Modification strategies of membranes with enhanced Anti-biofouling properties for wastewater Treatment: A review. (February 2022) - Kim, Andrew; Hak Kim, Jong; Patel, Rajkumar
Graphical abstract: Highlights: Biofilm formation and adhesion are mitigated using carbon-based nanomaterials. Nanomaterials such as graphene oxide and carbon quantum dots are mainly used. Functionalization with organic ligands and compositing with silver nanoparticles enhance the bactericidal ability. Membrane modifications reduce biofilm adhesion while increasing water permeance and salt/dye rejection. Abstract: This review addresses composite membranes used for wastewater treatment, focusing heavily on the anti-biofouling properties of such membranes. Biofouling caused by the development of a thick biofilm on the membrane surface is a major issue that reduces water permeance and reduces its lifetime. Biofilm formation and adhesion are mitigated by modifying membranes with two-dimensional or zero-dimensional carbon-based nanomaterials or their modified substituents. In particular, nanomaterials based on graphene, including graphene oxide and carbon quantum dots, are mainly used as nanofillers in the membrane. Functionalization of the nanofillers with various organic ligands or compositing the nanofiller with other materials, such as silver nanoparticles, enhances the bactericidal ability of composite membranes. Moreover, such membrane modifications reduce biofilm adhesion while increasing water permeance and salt/dye rejection. This review discusses the recent literature on developing graphene oxide-based and carbon quantum dot-based composite membranes for biofouling-resistant wastewater treatment.